Psychometric Characteristics of Arab university criteria As a Scale for TQM Indicators: Dhi Qar university as a Model - Abdulbari M. Al-Hamdani (University of Science and Technology, Yemen, 2014)
Psychometric Characteristics of Arab university criteria As a Scale for TQM Indicators: Dhi Qar university as a Model           Abstract:  The digital language and statistical treatments of quality measurements are priorities of empirical research, which concerns with systems of Total Quality Management‏ TQM and essentials of  institutional valuation and programmatic, Proceeding from the basis (The quality is the criteria and norms represent signs referring to the availability of the lowest level of statistical indications), the current research aims to find out if The norms of Arab Universities Union as a measurement of quality is a proper to University of Thi-Qar within norms Alsekoumtria (factor analysis, discriminatory force, statistical honesty), It aims  to know which of the subsidiary  measurements represent threats to the quality of the University of Thi-Qar and which do not, And which of faculties represent a low level of quality and which are the best ,  A sample of the performance of University's faculties And (another sample consists of 30 members including gender and faculty) were adopted to analyze university performance. whereas results of Arab Universities Union scale application were used  for the purpose of statistical analysis by using SPSS, through Factor analysis, the measure of Arab Universities Union characterized honestly in high level structure and appropriate to the reality of the University of Thi-Qar, In spite of the great differences accordance with relative weights of all component's paragraphs, but the all paragraphs and sub-measurements lead to one function (measuring of performance quality), It seemed that there are nine factors threaten the achievement of an acceptable level of quality, So the University of Thi-Qar must treat them if the University wished to achieve the required quality. So these threats were represented by (planning quality measure of Foundation, measurement of information systems quality, measurement of student services, measurement of universities quality, measurement of University Book quality, measurement of library services quality, measurement of scientific research, measurement of community services, measurement beneficiary's satisfaction). It was seemed, that there is a statistical sincerity by extracting the power of discriminatory of paragraphs through the usage of T- test for two independent samples using two extremes groups in the rate of 27%  for each one and it was seemed  that forms the Supreme group include samples of faculties (Science , Education Science Pure, Engineering and medicine).On the other hand The low Group are represented in the (physical education, Management, Economics, Agriculture and marshes in addition to Computers and Mathematics) and almost the signs of quality in which to be unavailable. Also by the research, It was verified of Statistical honesty through the critical value because of the correlation of each paragraph results with the total result of measurements by usage  Pearson's correlation coefficient, which also proved the suitable  of measurement for the application in accordance with the reality of the University of Thi-Qar. So this research has recommended some suggestions depending on results.